The Concept of “Rights” and the Reformulation of the Science of Maqāṣid in Islam - Saleh, Muhammad Al-Majthoub Muhammad (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2020)
The concept of “rights,” in its comprehensive understanding as gathered from the Qur’an, is not explicitly found conveyed as a standalone comprehensive concept in the science of uṣūl al-fiqh or the maqāṣid al-Sharīʿah. Rather, one will find that scholars of maqāṣid used it specifically in conveying the concept of maṣlaḥah (benefit or interests) and within the framework of realizing the higher objectives of the Shariʿah. Moreover, it was used exclusively in the context of the type of maṣlaḥah that was either unarticulated in the Shariʿah (i.e., maṣlaḥah mursalah) or that was derived through induction (istiqrā’). In other words, the notion of “rights” was employed in a technical sense and out of a need to formulate Shariʿah rulings and Islamic doctrine. It was needed for ijtihad and for extrapolating detailed rulings within what legal theorists had determined to be individual and collective rights and responsibilities. The notion of “rights” in maqāṣid thought was not viewed as a basis for the higher objectives of the Qur’an, but rather it was seen as governing the objectives of voluntary acts of the mukalif (legally responsible person). In essence, all the universal laws of the Shariʿah lead to “rights,” of which an Islamic way of life (in all its various and diverse aspects) correspond to. These universal laws should thus serve as a basis for all the laws and appropriate mechanisms needed to activate and develop a meaningful system for the realization of rights in the current state of affairs. This article therefore treats the Qur’anic worldview’s great attention to the notion of rights, to the extent of establishing upon its articulation of rights a system of human objectives. The notion of rights in the Qur’anic context, in fact, covers various aspects of life, such that it can be said that the objectives of the Qur’an are essentially the objectives of rights. It is this scientific orientation that we hope will create another area in the fiqh of maqāṣid, doing so at a moment in which we pursue the objectives of the Qur’an and their fundamental import.